Discovery of a novel series of pyridine and pyrimidine carboxamides as potent and selective covalent inhibitors of Btk. Issue 21 (15th November 2018) - Caldwell, Richard; Liu-Bujalski, Lesley; Qiu, Hui; Mochalkin, Igor; Jones, Reinaldo; Neagu, Constantin; Goutopoulos, Andreas; Grenningloh, Roland; Johnson, Theresa; Sherer, Brian; Gardberg, Anna; Follis, Ariele Viacava; et al.
Graphical abstract: Highlights: Novel series of covalent and selective pyridine and pyrimidine Btk inhibitors was discovered. Compounds were based on the elaboration of a fragment that bound to the ATP active site of Btk. Optimization led to compound17 with excellent biochemical, cellular, and whole blood potency. Compound17 did not attain sufficient oral bioavailability in a low dose mouse pK study to be considered a lead compound. Abstract: Btk is an attractive target for the treatment of a range of Bcell malignancies as well as several autoimmune diseases such as murine lupus and rheumatoid arthritis. Several covalent irreversible inhibitors of Btk are currently in development including ibrutinib which was approved for treatment of B-cell malignancies. Herein, we describe our efforts using X-ray guided structure based design (SBD) to identify a novel chemical series of covalent Btk inhibitors. The resulting pyridine carboxamides were potent and selective inhibitors of Btk having excellent enzymatic and cellular inhibitory activity.